2019
DOI: 10.17576/jsm-2019-4809-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tiliacora triandra Leaf Extract on Glycemic Control in Mice with High Sugar Intake

Abstract: Prediabetes is associated with sugar-sweetened beverages and sugar-rich processed foods. High sugar intake (HSI), which is represented as save dose, may silently alter the glycemic control. The present study investigated the effect of HSI and Tiliacora triandra (TT21) leaf extract on the glycemic control in mice. Eighteen male ICR mice were divided into three groups of Control-HSI, HSI-TT300 and HSI-TT600 that received 4 weeks of 30% glucose with a vehicle of T. triandra leaf extract 300 and 600 mg/kg, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, ong-asa et al [35] reported that T. triandra leaf extracts at 300 and 600mg/kg doses, Significantly restored motor coordination deficits induced by CISP and rats showed marked improvement in thermal/chemical hyperalgesia and mechanical allodynia [43] respectively, increased glycogen, whereas reduced blood glucose and serum insulin rates in muscle and liver in mice after administration for four weeks (Table 3). ese effects involved an enhancement in glucose clearance, a decrease in glucose intestinal absorption, and an increase in peripheral insulin sensitivity in comparison to high sugar intake mice that were used as a positive control for 4 weeks.…”
Section: Antidiabetic Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, ong-asa et al [35] reported that T. triandra leaf extracts at 300 and 600mg/kg doses, Significantly restored motor coordination deficits induced by CISP and rats showed marked improvement in thermal/chemical hyperalgesia and mechanical allodynia [43] respectively, increased glycogen, whereas reduced blood glucose and serum insulin rates in muscle and liver in mice after administration for four weeks (Table 3). ese effects involved an enhancement in glucose clearance, a decrease in glucose intestinal absorption, and an increase in peripheral insulin sensitivity in comparison to high sugar intake mice that were used as a positive control for 4 weeks.…”
Section: Antidiabetic Effectsmentioning
confidence: 98%
“…e n-hexane extracts of twigs of T. triandra were reported to exhibit promising nitric oxide, α-amylase, and α-glucosidase inhibition activities [3]. Furthermore, the leaf extract of this plant also demonstrated hypoglycemia in the mouse model that was fed with a high sugar intake followed by increased glycogen storage in both the liver and muscle and reduced serum insulin level [35].…”
Section: Antidiabetic Effectsmentioning
confidence: 99%